Cave-dwelling Neobisiidae in South China Karst, with descriptions of twelve new species of Bisetocreagris (Pseudoscorpiones, Neobisiidae) from Guizhou Province - Feng, Zegang; Zhang, Feng; Chen, Jun (Zootaxa, 2023)
Twelve new troglomorphic pseudoscorpion species of the genus Bisetocreagris Ćurčić, 1983 (Family Neobisiidae) are described based on specimens collected from karst caves in Guizhou Province, China: Bisetocreagris ampla sp. nov. from Hei Cave (Zunyi City), B. aspera sp. nov. from Tu Cave (Tongren City), B. brevis sp. nov. from Yehu Cave (Tongren City), B. changbing sp. nov. from Sanyuan Cave and Guanyin Cave (Zunyi City), B. chumi sp. nov. from Tufei Cave (Zunyi City), B. grandis sp. nov. from Wulibeidadong Cave (Bijie City), B. jiangi sp. nov. from Anjialin Cave (Tongren City), B. longidigitata sp. nov. from Mao’er Cave (Guiding County), B. que sp. nov. from Yanggong Cave (Sandu County), B. sanmen sp. nov. from Sanmen Cave (Zunyi City), B. xishui sp. nov. from Dongkoushan Cave (Zunyi City), B. tenuipalma sp. nov. from Sanjie Cave (Zunyi City). Detailed diagnoses, descriptions, and illustrations are provided for all species.